Instructional techniques of geographical tours in high school (Pedagogy of Higher and Secondary Education, 2012)
Ganchuk E. Instructional techniques of geographical tours in high schoolMethodical receptions of group informative activity of students are opened at tours from geography are conducted educational. Educasrional excursion is a form of the organization of teaching and educational work on geography which allows to organization of teaching and studying be students of the different phenomena, subjects, processes under natural conditions, museums, at exhibitions, ect. and makes influence on development of informative activity of students, its motivational, substantial and procedural aspects.
Keywords: geographical excursion; group work; methodical receptions